KAJIAN MOTIF BATIK GONGGONG CV LAWANA DI TANJUNG PINANG - Nancy Hanna Lumban Gaol (Ornamen, 2022)
Gonggong CV Lawana in Tanjung Pinang using a textile design method approach. This research is formulated in one question "How is the design of the Batik Gonggong motif in the Production of Batik Gonggong CV Lawana, Tanjung Pinang with a textile design method approach through aesthetic, material, process, function, and fashion aspects?". This research uses a descriptive qualitative research method with a textile design method approach. Data analysis techniques using interactive analysis models include data reduction, data presentation, and concluding. The results of the research reveal the stages that are passed in designing based on aesthetic aspects, materials, process functions, and supporting aspects, namely fashion. (1) The aesthetic aspect that is considered in the main and supporting motifs, especially the main motif of Batik Gonggong CV Lawana has identical characteristics with the character of a snail shell that bulges in its belly. (2) The material aspect is a consideration in selecting the type of yarn fiber, the structure of the weave, nature and absorption capacity or suitability of the fabric as well as the different alternative fabrics for stamped and written batik products. (3) The process aspect of Batik Gonggong begins with determining the design from the main source of inspiration, the shell of the barking snail, the design will go through a sublimation process, then continue to be produced in certain quantities. (4) Functional aspects are related to consumers who use the product as a choice of use, as regional souvenirs, uniforms, and fashion. (5) The fashion aspect is found in the development of motifs through three periods ranging from natural suggestion patterns, creative patterns, and combined patterns. The development of the coloring technique, namely gradation is done by brushing using a sponge with a combination of giving light and dark colors which when soaked will fade and produce a gradation effect.